Analisis Empiris Work Life Balance, Work Engagement, dan Lingkungan Kerja sebagai Determinan Kepuasan Kerja Guru Gen Z (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Rapid changes in the digital world are pushing educators to adopt technology, but also creating complex administrative responsibilities that impact job satisfaction, an important element for professional performance and sustainability. One of the main phenomena is the significant gap between Generation Z's (Gen Z, born between 1997-2012) expectations of work-life balance and the actual conditions in the teaching world, which is considered ‘high risk’. Although Gen Z shows enthusiasm, they are trapped in pressure and fatigue due to the enormous burden of non-teaching tasks, as well as feudal and unsupportive school conditions, which lead to low Work Engagement. The lack of studies focusing on the influence of Work-life Balance, Work Engagement, and Work Environment on the Job Satisfaction of Gen Z teachers in Indonesia in particular is a gap in research. This study aims to bridge this gap, given the characteristics of Gen Z who desire flexibility and a supportive atmosphere. This quantitative research plays an important role in providing empirical contributions and as a basis for the development of education policies in formulating strategies to improve teacher welfare that are responsive to the demands of the new generation.